Creativity and Urban Development: the Chinese perspective within UNESCO Creative Cities Network - Yajing Liu (2024)
To keep up with the successive changes in cities, creative industries has becomefundamental for cities on sustainable development and growth in worldwide. Using a qualitative research methodology, based on bibliographic researchandanalysis, this dissertation begins by delving into the domains of creativity and creativeindustries, underscoring their profound significance within the broader context of urbandevelopment. Then it illuminates the UNESCO Creative Cities Network (UCCN) anditspivotal role in advancing cultural diversity and sustainable development within the extent ofChinese creative cities. Then this work explores the membership of eighteen Chinese cities in UCCNacrosssix of seven distinct themes, it becomes evident that creativity acts as the driving force behindtheir transformative journeys. Nanjing, City of Literature, celebrates its literary legacythat spans millennia, nurturing both indigenous classics and global literary laureates. Shenzhen, Beijing, Shanghai, Wuhan and Chongqing designated as City of Design, exemplifyhowcreativity catalyzes economic growth, technological innovation, and cultural enrichment. Hangzhou, Suzhou, Jingdezhen and Weifang, as City of Crafts and Folk Art, meticulouslypreserve age-old traditions in silk, tea, porcelain, and bronze sculptures. Qingdao, recognizedas City of Film, stands as a hub for film festivals and boasts the world’s largest filmandtelevision industry park. Changsha, City of Media Arts, pioneers’ technology-drivencultural experiences, from digital displays to virtual historical recreations. Chengdu, Shunde, Macao, Yangzhou, Huai’an and Chaozhou, designated as City of Gastronomy, present the art ofharmonizing diverse flavors and promote active community participation in gastronomy. The analysis to the Chinese cities that belong to the UCCN is used as a showcaseof harmonizing diverse flavors and promote active community participation in gastronomy. The analysis to the Chinese cities that belong to the UCCN is used as a showcaseof the potential of Xi’an to become a City of Music, these two sections highlight the undeniablerole of creative industries to facilitate sustainable urban development, present a visionof moreChinese cities joining the UCCN in the future, emphasize the cultural and creative strengthofChina and wish to garner increased attention for China in the world.